From Lexical to Functional: The Grammaticalization of Temporal Particles in the Tarifit Dialect of Temsamane - Lahyany, Tarik (International Journal of Language and Literary Studies, 2025)
This article examines the grammaticalization of three periphrastic tense particles in the Tarifit dialect of Temsamane (henceforth TT) . It is shown that in Stage 1, the semantic value of progressivity primarily triggered the grammaticalization of these temporal elements. One of them has fully developed into a temporal particle, evidenced by its capacity to host clitics, while the other two remain in the process of grammaticalization. This development gave rise to a tripartite temporal system: past derived from a copulative auxiliary, present from a locative predicate, and future from a lexical verb that has coalesced to a temporal particle. In Stage 2, other perfect forms emerged from these grammaticalized particles, and consequently allowed for the expression of progressive and stative meanings within both past and future contexts. The framework adopted in this study is the Minimalist Program (Chomsky, 1995).